UPAYA MENINGKATKAN KEMAMPUAN MENYIMAK CERITA SISWA MELALUI MEDIA PEMBELAJARAN AUDIO VISUAL DI KELAS V SDN GUNUNG BUNDER 05 - Yayah Choeriyah; Suwilah; Abdul Kholik; Teguh Prasetyo (AL - KAFF: JURNAL SOSIAL HUMANIORA, 2023)
: Based on observations on Indonesian language learning in grade V SDN Gunung Bunder 05, Pamijahan District, it was found that problem information included that students did not concentrate on listening, were not interested in learning and did not focus on what the teacher said. Especially when the teacher asked questions, many students were still confused and the students had difficulty answering the story questions. This is why the results of students' listening ability are still low. Of the 29 students of class V, 13 students or 44.83% who scored above 67, while 16 students or 55.17% scored below 67.The objectives to be achieved in this study were: to determine the extent to which the use of Audio Visual Learning Media in improving the ability to listen to stories of fifth grade students of SDN Gunung Bunder 05, Pamijahan District. The method used in this research is Classroom Action Research (PTK). Based on the post-action test cycle I, it can be seen that there is an increase in the average score of completeness from the pre-action test to the post-action test in cycle I, namely from 44.83% (13 students) to 68.97%. (20 students) Then in cycle II there was another increase in the average completeness (KKM) to 96.30% (26 students). The results of this study found that the use of audio-visual media can improve the results of children's listening ability. All grade V students of SDN Gunung Bunder 05 Pamijahan-Bogor have met the minimum score limit, so the research was not continued to cycle III, and was stopped in cycle II. Likewise with teachers. Based on the results of the assessment in reflection activities carried out by two observers as peers in assessing teacher activeness in cycles 1 and 2, it was concluded that there was a change in teacher activeness in cycle 2 compared to teacher activeness in cycle 1. This is evidenced by the acquisition of an average score. The average teacher activeness shows a number of 6.9 in cycle 1 and has increased to 7.1 in cycle 2.Thus, teacher activity is declared goodcycle 2 compared to teacher activity in cycle 1. This was evidenced from the acquisition of the average score the average of teacher activeness which shows a number of 6.9 in cycle 1 and an increase to 7.1 in cycle 2. Thus for teacher activeness declared good.